2018
DOI: 10.1021/acs.iecr.7b04609
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Molecular Weight Dependence on Lubricating Particle–Particle Interactions

Abstract: Using ultra-thin surface coatings of water-soluble polymers to modify interfacial friction is relatively new, but may offer routes to form beneficial coatings whilst using significantly lower polymer concentrations. In the current study, silica surfaces were modified by the physisorption of poly(vinylpyrrolidone) (PVP) from water solution. Four polymer samples with different molecular weights ranging from 8 kDa to 1300 kDa, were examined here. Optical reflectivity measurements showed that the saturated surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…[22] Our previous study confirmed the stability of PVP to water rinse-off, with negligible mass removed following adsorption on silica. [49] For the current experimental conditions the adsorbed PVP was shown to be stable to the sample washing procedure outlined in Yu et al [22] and throughout the duration of the study. [36,37] One advantage of combined Langmuir trough + BAM is that the structural changes associated with compression of the particle-laden interface can be measured in-situ without the need for ex-situ analysis of a Langmuir-Blodgett film.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…[22] Our previous study confirmed the stability of PVP to water rinse-off, with negligible mass removed following adsorption on silica. [49] For the current experimental conditions the adsorbed PVP was shown to be stable to the sample washing procedure outlined in Yu et al [22] and throughout the duration of the study. [36,37] One advantage of combined Langmuir trough + BAM is that the structural changes associated with compression of the particle-laden interface can be measured in-situ without the need for ex-situ analysis of a Langmuir-Blodgett film.…”
Section: Methodsmentioning
confidence: 74%
“…2), this observed independence likely results from the deposited PVP layer around the nano silica particles. In our recent study we showed that two PVP-coated surfaces (silica) produce a lubrication effect when compressed together, [49] with the lubrication effect maintained, albeit to a reduced effect, when polymers are submerged in solutions of increasing electrolyte concentration. [50,51] As such, the particleparticle contacts become mobile at a critical compressional stress, allowing the film to reorganize and densify to an almost self-similar structure before eventually collapsing (buckling or wrinkling).…”
Section: Resultsmentioning
confidence: 96%
“…18 Our previous study confirmed that the adsorbed PVP layer was stable and resistant to water rinse-off throughout the duration of the test. 18,21,40 Quartz Crystal Microbalance with Dissipation (QCM-D) Monitoring. The adsorption of saponin β-escin on silica and PVP-coated silica was studied using an E4 QCM-D from Q-Sense (Gothenburg, Sweden) at 25 ± 0.02 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The sensor cleaning procedure is outlined in a previous publication. 40 All measurements began by running the background fluid until a stable baseline was attained before pumping the test solution into the sensor cell. The changes in frequency (Δf) and dissipation (ΔD) were measured simultaneously at different overtones.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The quartz crystal microbalance is a tool frequently used to study soft matter systems providing insight into deposited/adsorbed layer properties, 2 interactions between chemical and/or biological species, and the stability of deposited/adsorbed layers under different physicochemical conditions. [3][4] There is growing interest to study the influence of point contact loads (particles) on the QCM sensor resonance properties, with complexity now extending to probe the resonance properties in the presence of colloidal dispersions.…”
Section: Introductionmentioning
confidence: 99%